The extract of an herbal medicine Chebulae fructus inhibits hepatocellular carcinoma by suppressing the Apelin/APJ system - Liu, Yu-Xi; Wang, Lu; Zhang, Cong-Ying; Long, Kai-Hua; Liu, Jing; Liu, Shuai; Wang, Yuan; Li, Ye; Liu, Yang; Zhang, Hong (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma (HCC) has been a highly common and pathological disease worldwide, while current therapeutic regimens have limitations. Chebulae Fructus, a common herbal medicine in Asia, has been documented to exert potential therapeutic effects on HCC in ancient medicine clinical practice. However, the molecular mechanism underlying its inhibitory effects on HCC requires further investigation. The results of this study demonstrate that the aqueous extract of Chebulae Fructus (CFE) effectively suppressed the proliferation and activity of HepG2 and PLC/PRF/5 HCC cells. CFE also induced apoptosis, and suppressed the migration and invasion abilities of these cells. Furthermore, CFE exhibited inhibitory effects on tumor growth in both H22 and PLC/PRF/5 mouse models, as well as in an HCC PDX model which is derived from patient tumor samples. Through transcriptomics analysis, it was identified that CFE treatment specifically suppressed the Apelin/APJ system. Results of qRT-PCR, ELISA, IHC staining, and Western blotting, further verified the effects of CFE in suppressing the Apelin/APJ system. To investigate the role of the Apelin/APJ system in mediating the effects of CFE treatment, an APJ-overexpressed cell model is established. Interestingly, it was found that the overexpression of APJ significantly diminished the inhibitory effects of CFE on HCC in vitro. In conclusion, this study provides compelling evidence that CFE exerts significant anti-HCC effects in cell and animal models. Moreover, our findings suggest that the Apelin/APJ system may play a vital role in the therapeutic effects of CFE against HCC.